Surviving Between Hosts: Sporulation and Transmission - Michelle C. Swick; Theresa M. Koehler; Adam Driks (2016)
To survive adverse conditions, some bacterial species are capable of developing into a cell type, the "spore," which exhibits minimal metabolic activity and remains viable in the presence of multiple environmental challenges. For some pathogenic bacteria, this developmental state serves as a means of survival during transmission from one host to another. Spores are the highly infectious form of these bacteria. Upon entrance into a host, specific signals facilitate germination into metabolically active replicating organisms, resulting in disease pathogenesis. In this article, we will review spore structure and function in well-studied pathogens of two genera, Bacillus and Clostridium, focusing on Bacillus anthracis and Clostridium difficile, and explore current data regarding the lifestyles of these bacteria outside the host and transmission from one host to another.